International Handbook of Research on Teachers and Teaching
1200 p.
Keywords: The International Handbook of Research on Teachers and Teaching provides a fresh look at the ever changing nature of the teaching profession throughout the world. This collection of over 70 original articles addresses a wide range of issues that are relevant for understanding the present educational climate in which the accountability of teachers and the standardized testing of students have become dominant. The international collection of authors brings to the handbook a breadth of knowledge and experience about the teaching profession and a wealth of material across a number of comparative dimensions, such as between developed and developing countries and between Eastern and Western cultures. In addition, many articles address the emerging challenges to education and to the lives of teachers which are brought about by the globalization trends of the 21st Century.